2012
DOI: 10.1021/ja211368u
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Evidence for and Characterization of a Trinuclear Ferroxidase Center in Bacterial Ferritin from Desulfovibrio vulgaris Hildenborough

Abstract: Ferritins are ubiquitous and can be found in practically all organisms that utilize Fe. They are composed of 24 subunits forming a hollow sphere with an inner cavity of ~80 Å in diameter. The main function of ferritin is to oxidize the cytotoxic Fe2+ ions and store the oxidized Fe in the inner cavity. It has been established that the initial step of rapid oxidation of Fe2+ (ferroxidation) by H-type ferritins, found in vertebrates, occurs at a diiron binding center, termed ferroxidase center. In bacterial ferri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 70 publications
4
10
0
Order By: Relevance
“…These results suggested to us that H 2 O 2 is the product of the ferroxidase reaction in HuHF and PfFtn, consistent with previous reports for HuHF20–21 and PfFtn 15b. We conclude that simultaneous oxidation of three Fe II ions in each ferroxidase center and the production of water only (reaction (2), Figure 4), as proposed for bacterial ferritin,2b, 11, 12 is not valid for PfFtn, although its ferroxidase center has a coordination environment identical to that of bacterial ferritin (Figure S1). One explanation is that as the amount of Fe II increases, H 2 O 2 produced during the ferroxidase reaction reacts with other components in the reaction mixture to produce oxygen, and, as a result, the stoichiometry decreases.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These results suggested to us that H 2 O 2 is the product of the ferroxidase reaction in HuHF and PfFtn, consistent with previous reports for HuHF20–21 and PfFtn 15b. We conclude that simultaneous oxidation of three Fe II ions in each ferroxidase center and the production of water only (reaction (2), Figure 4), as proposed for bacterial ferritin,2b, 11, 12 is not valid for PfFtn, although its ferroxidase center has a coordination environment identical to that of bacterial ferritin (Figure S1). One explanation is that as the amount of Fe II increases, H 2 O 2 produced during the ferroxidase reaction reacts with other components in the reaction mixture to produce oxygen, and, as a result, the stoichiometry decreases.…”
Section: Resultssupporting
confidence: 92%
“…In the model for eukaryotic H and M ferritin, two Fe II ions are simultaneously oxidized in the ferroxidase center to form a blue intermediate, which subsequently decays to the Fe III products and hydrogen peroxide (Figure 1 C). 2a, 8b,10 For Escherichia coli ferritin A (EcFtnA)11 and Desulfovibrio vulgaris ferritin (DvFtn),12 a different model proposes that three Fe II ions (two in the ferroxidase center and one in the gateway site, commonly referred to as the Fe C site in bacterial and archaeal ferritin5a, 6,1 3) are simultaneously oxidized by one molecular oxygen,2b,111 2 and that water is produced (Figure 1 C). In this model the origin of the fourth electron necessary for the reduction of molecular oxygen to water is not specified.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, consistent with this speculation is our previous Mössbauer study of PfFtn, in which we found that the Mössbauer parameters of Fe(II) in site C before the addition of dioxygen are different than those after the addition of dioxygen (Table 1) 10. The importance of site C for efficient catalysis of Fe(II) oxidation has been reported for other ferritins namely Escherichia coli ferritin A 25, 26 and Desulfovibrio vulgaris Hildenborough ferritin 27.…”
Section: Discussionsupporting
confidence: 89%
“…The amino acid sequences of five ferritins (Helicobacter pylori, HpF; Archaeoglobus fulgidus, AfFtn; Pyrococcus furiosus, PfFtn; Desulfovibrio vulgaris , DvFtn and Escherichia coli, EcFtnA) all show highly conserved C-site residues, suggesting an important function of this site (3541,50). Indeed, the C-site of EcFtnA is not a passive player in the ferroxidase activity of the protein but rather modulates the stoichiometric and kinetic properties of the protein.…”
Section: Discussionmentioning
confidence: 99%